The European Socio-Economic Model. Differences to the USA and Changes over Time - Karl Aiginger; Alois Guger (Austrian Institute of Economic Research (WIFO), 2005)
This paper analyses the main characteristics of the European Socio-Economic Model. We discuss how the model varies across countries within Europe, examine how the model has changed over time and compare the European model with the corresponding US model. While the differences with regard of growth dynamics are very small in the long run (1960 to 1990), growth rates diverge in the past 15 years. Performance differences as well as the reforms which have taken place, allow us to delineate elements of a "Reformed European Model", which on the one hand upholds important characteristics of the European Society, but on the other hand can still be competitive in the globalised economy.
Keywords: 330; Wirtschaftswachstum; Wirtschaftspolitik; Vergleich; EU-Staaten; USA